2008
DOI: 10.1086/589886
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Investigation of the Effect of Latitude on Avian Life Histories

Abstract: Online enhancements: appendixes.abstract: Tropical birds lay smaller clutches than birds breeding in temperate regions and care for their young for longer. We develop a model in which birds choose when and how often to breed and their clutch size, depending on their foraging ability and the food availability. The food supply is density dependent. Seasonal environments necessarily have a high food peak in summer; in winter, food levels drop below those characteristic of constant environments. A bird that cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 78 publications
4
92
2
1
Order By: Relevance
“…Our findings cast doubt on a long-standing view of the association between climatic zone (latitude) and sexual promiscuity in birds [10,18,23], and contrast with results of previous studies that found smaller relative testis size in tropical birds [11] or a general decrease in EPP (another proxy measure of sperm competition) with decreasing latitude [18]. However, the general supposition of low intensity of sperm competition in the tropics seems to have been drawn from rather weak and indirect evidence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings cast doubt on a long-standing view of the association between climatic zone (latitude) and sexual promiscuity in birds [10,18,23], and contrast with results of previous studies that found smaller relative testis size in tropical birds [11] or a general decrease in EPP (another proxy measure of sperm competition) with decreasing latitude [18]. However, the general supposition of low intensity of sperm competition in the tropics seems to have been drawn from rather weak and indirect evidence.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, tropical birds do not migrate for long distances, whereas EPP rates have been suggested to increase with migration distance and associated effects of short breeding seasons, high breeding synchrony and rapid pair formation [17,18]. On the other hand, low demands for parental care seem to be associated with increased sperm competition in birds [14,19,20], and many tropical birds are characterized by reduced parental investments into a single breeding attempt [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the wellknown link between high temperature, solar radiation and humidity and the reduction in milk production in dairy cattle (Thompson, 1973;King et al, 2006;Nassuna-Musoke et al, 2007), sheep Ovis aries (Abdalla et al, 1993) and pigs Sus scrofa (Black et al, 1993;Renaudeau and Noblet, 2001), heat dissipation limitations might help explain latitudinal and altitudinal trends in clutch sizes of birds (larger where it is colder) (Bohning-Gaese et al, 2000;Cooper et al, 2005) (but see McNamara et al, 2008). It could also provide a reason why humans, one of the few mammals that can sweat profusely, are able to outrun pretty much any running game in the midday heat (Heinrich, 2001).…”
Section: Proximate Constraints On Metabolic Ceilingsmentioning
confidence: 99%
“…A classic example is the increase of clutch size with increasing latitude, as documented by Moreau (1944), Lack (1947Lack ( , 1948, Skutch (1949Skutch ( , 1985, and Jetz et al (2008). There is a large body of literature on the evolution of bird life-history traits (Cody 1966, Owens and Bennett 1995, Ricklefs 2000 and on the evolutionary underpinnings of a latitudinal gradient in clutch size (Murray 1985, Martin et al 2006, McNamara et al 2008. Studying the evolutionary processes behind the gradient is a worthwhile endeavor, but there is a simpler problem, which also deserves attention, of how such a pattern can be maintained.…”
Section: Introductionmentioning
confidence: 99%